A new production process for soft actuators and sensors based on dielectric elastomers intended for safe human robot interaction - Reitelshöfer, Sebastian; Landgraf, Maximilian; Gräf, Daniel; Bugert, Larissa; Franke, Jörg (2015 IEEE/SICE International Symposium on System Integration (SII), 2015)
Dielectric elastomers are the subject of intense research in material science. A large number of publications describe artificial muscles based on dielectric elastomer actuators as a promising alternative for an energy efficient, lightweight and flexible actuation architecture. Dielectric elastomer actuators could improve and extend the capabilities of robots in terms of soft kinematics for the direct physical interaction between humans and robots. They could also improve the dynamical performance and the eligibility for energy autarkic operation of robotic systems. Another field of application are dielectric elastomer sensors that can bear and detect large deformation. However, up to now dielectric elastomer actuators and sensors are not available on a large scale with reproducible characteristics. The focus of this contribution lies on a new automated production process using Aerosol-Jet-Printing for dielectric elastomer actuators and sensors with very favorable characteristics resulting from the additive manufacturing aiming at an improved availability of such sensors and actuators.
Keywords: deformation; electroactive polymer actuators; human-robot interaction; industrial robots; rapid prototyping (industrial); three-dimensional printing; additive manufacturing; aerosol-jet-printing; artificial muscles; automated production process; deformation detection; dielectric elastomer actuators; dielectric elastomer sensors; energy autarkic operation; energy efficient lightweight flexible actuation architecture; human-robot physical interaction; robot kinematics; robotic systems; soft actuators; soft sensors; Actuators; Dielectrics; Printing; Sensor phenomena and characterization; Service robots